The Application of Quizizz Game to Enhance the Cognitive Abilities of Group B Children at TK PGRI 1 Mataram - Namiratun Sa'rah; Gunawan Gunawan; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2025)
This research aims to enhance children's cognitive abilities through the implementation of the Quizizz game. Cognitive ability is a crucial developmental aspect that must be stimulated from an early age. At this stage, appropriate stimulation is essential to assist children in developing these skills. One effective method for stimulating early childhood cognitive development is game-based learning, such as Quizizz. This study employed the Classroom Action Research (CAR) method, following the Kemmis and McTaggart model, which was conducted in two cycles. The subjects of this research consisted of 14 children. Data collection techniques included observation, cognitive tests, and documentation. The results indicated a significant improvement in children's cognitive abilities from the pre-cycle to Cycle II. In the pre-cycle, classical mastery reached 52.98%. This increased to 62.50% in Cycle I and reached 88.84% in Cycle II. Consequently, the application of the Quizizz game is proven effective in enhancing early childhood cognitive abilities in a fun and interactive manner.